Paradigma Reinterpretasi Konsep سِتَّةَ أَيَّامٍ dalam QS. Hud: 7 dan Relevansinya dengan Konsep سَبْعَةُ أَيَّامٍ dalam Budaya Kontemporer - Solihin Solihin; Komarudin Sassi (Indo-MathEdu Intellectuals Journal, 2026)
QS. Hud: 7 mentions the phrase سِتَّةَ أَيَّامٍ (six days or six periods) in the context of the creation of the heavens and the earth, which has long been the object of study by commentators, both classical and contemporary. On the other hand, the concept of سَبْعَةُ أَيَّامٍ (seven days) has been deeply rooted in global culture as a week system that regulates the rhythm of modern human life. This study aims to analyze the paradigm of reinterpretation of سِتَّةَ أَيَّامٍ in QS. Hud: 7 and other similar verses, such as QS. al-A‘raf: 54, QS. Yunus: 3, QS. al-Furqan: 59, QS. al-Sajdah: 4, QS. Qaf: 38, and QS. al-Hadid: 4, using the perspective of tafsir mawḍū‘ī, scientific, and contextual, while examining its relevance to the concept of seven days in contemporary culture. This study uses a descriptive qualitative approach through library research based on tafsir mawḍū‘ī, and integrates Nurcholish Madjid's thoughts in his work Islam, Doctrine and Civilization as a theological basis. The results of the analysis show that the term أَيَّام in QS. Hud: 7 does not refer to a twenty-four-hour calendar day, but rather to a cosmological phase or stage that is in accordance with the findings of modern science. In addition, this study found an epistemological bridge between the concept of six periods of creation in the Qur'an and the universal seven-day week system. This integrative reinterpretation provides a more contextual theological foundation for Muslims in understanding the concept of time and the week system used in contemporary life